ANALISIS EFEKTIVITAS PENERAPAN JADWAL RETENSI ARSIP (JRA) TERHADAP PENYUSUTAN ARSIP INAKTIF PT XYZ - Zulfa Dwi Fauziah; Munawaroh; Ferry Setyadi Atmadja (Jurnal Riset Multidisiplin Edukasi, 2026)
This study analyzes the effectiveness of Archive Retention Schedule (ARS) implementation in the process of reducing inactive archives at a port company. The accumulation of 9,442 boxes of inactive archives indicates suboptimal ARS implementation. Using a descriptive qualitative approach with case study method, data were collected through in-depth interviews with four informants (Assistant Manager of HR, General Affairs and Household Administration Sub-Division and three archival staff), field observations, and documentation studies. Data validity was tested using source, technique, and theory triangulation. Results show that ARS implementation has not been effective in terms of archival policies and procedures. Although ARS and SOPs are available as formal guidelines, their implementation remains partial and only consistent at the storage and transfer stages, while the reduction stage has not been implemented. Six main obstacles were identified: low management support, limited human resource competencies, limited facilities and infrastructure, non-optimal data recording systems, complex internal bureaucracy, and reactive reduction patterns oriented towards cost efficiency. This ineffectiveness results in the accumulation of inactive archives, storage space and cost inefficiency, difficulties in archive retrieval, and non-compliance with archival regulations. This study recommends strengthening management commitment, improving HR competencies through technical archival training, improving archive data recording systems, simplifying internal licensing mechanisms, and implementing continuous monitoring.